Promising Druggable Target in Head and Neck Squamous Cell Carcinoma: Wnt Signaling - Aminuddin, Amnani; Ng, Pei Yuen (Frontiers in Pharmacology, 2016)
Canonical Wnt signaling pathway, also known as Wnt/β-catenin signaling pathway, is a crucial mechanism for cellular maintenance and development. It regulates cell cycle progression, apoptosis, proliferation, migration and differentiation. Dysregulation of this pathway correlates with oncogenesis in various tissues including breast, colon, pancreatic as well as head and neck cancers. Furthermore, the canonical Wnt signaling pathway has also been described as one of the critical signaling pathways for regulation of normal stem cells as well as cancer cells with stem cell-like features, termed cancer stem cells. In this review, we will briefly describe the basic mechanisms of Wnt signaling pathway and its crucial roles in normal regulation of cellular processes as well as in the development of cancer. Next, we will highlight the roles of canonical Wnt signaling pathway in the regulation of cancer stem cell properties namely self-renewal, differentiation, metastasis and drug resistance abilities, particularly in head and neck squamous cell carcinoma. Finally, we will examine the findings of several recent studies which explore druggable targets in the canonical Wnt signaling pathway which could be valuable to improve the treatment outcome for head and neck cancer.